Participation and Spatial Analysis to make Cities Resilient to Climate Change. The Historic Center of Genoa - Bruno, Fabrizio; Spadaro, Ilenia; Paoli, Federica; Poggio, Barbara; Pirlone, Francesca (Contesti. Città, territori, progetti, 2026)
Climate change represents one of the most urgent challenges of the 21st century; Historic Centers are highly vulnerable to its effects, and, in a scenario of worsening climate regimes, it is crucial to explore innovative methods and tools to promote adaptation to climate change specific to these multi-risk contexts. However, research in this field is still underdeveloped, especially when it comes to the active involvement of territorial stakeholders in identifying and managing multiple climate-related risks-prone areas. This paper proposes a participatory methodology developed within the EU-funded HERIT ADAPT project aims at analyzing the criticalities affecting Historic Centers and co-designing interventions for the multi-risk adaptation of them to climate change. The application of the methodology to the case study of the Historic Centre of Genoa is presented and first results are reported. The goal is to test and generalize the approach to make it as objective and replicable as possible, by identifying processes and technological tools, as well as categories of data that can be easily found in official databases related to historical urban contexts.